Electronic Cigarettes on Sperm Quality: Review in Animal and Human Study - Nahak, Teresita Marselina; I Gusti Ngurah Pramesemara (Indonesian Andrology and Biomedical Journal, 2023)
Electronic cigarettes that are currently popular are used as nicotine replacement therapy. There are several substances contained in electronic cigarette liquid that have carcinogenic effects. These substances can also increase free radicals which in turn can cause oxidative stress. Nicotine, propylene glycol, and glycerin can cause disturbances in male reproductive function. Infertility can occur due to lifestyle factors, one of which is smoking. Nicotine found in cigarettes can reduce sperm quality, including concentration, mobility, viability, and sperm morphology. The purpose of this study was to determine the effect of electronic cigarettes on sperm quality. The research method uses a literature review system. The twelve studies that are in accordance with the topic of discussion are experimental studies on mice and rats, two studies on human, and one study on both human and rats. Five journals showed a significant decrease in sperm count and testosterone serum level, three other journals showed a significant decrease in sperm morphology and viability, six journals showed a decrease in sperm motility, seven journals showed a significant impairment of testis histological structure, four journals showed a decrease of steroidogenesis enzymes, and one journal showed a significant increase of DNA fragmentation due to the use of electronic cigarettes. Electronic cigarettes had an effect on sperm quality.